Optimization of Diagnostic and Treatment Tactics Regarding Impacted Lower Third Molars with the Employment of Author’s Program of Computer Modelling - Vares Y.; Kyyak S. (Львівський клінічний вісник)
Introduction. A significant percentage of intra- and postoperative complications requires the search for the new approaches to making a decision on the appropriateness and choice of methods for atypical removal of the lower third molars, namely, the definition of objective criteria for preoperative prognosis of the complexity and trauma of the surgical intervention. Searching for the new approaches in making decision for removal and giving preference to this or that method of atypical removal is forced by continuously great number of intra- and postoperative complications. One of the main issues to consider is the determination of objective methods to predict the difficulty and level of injury of surgical removal. Aim. Based on the analysis of the current publications on the issue of the diagnosis and treatment regarding the retained lower third molars, the re is proposed an author program using computer modeling of retention and operations in cases of the atypical removal of teeth. Material and methods. Taking into account previously published research results and own previous long experience on the operation of atypical removal of lower “wisdom teeth”, we initiated the creation and introduction into clinical practice of computer the programs «X-ray analyzer» for the diagnosis of the retention of lower third molars, planning and prognosing of the course of the operation on their removal and analysis of possible postoperative complications, etc., on which we have received a patent of Ukraine for utility model. Results. Hence, we created and implemented a computer program for the evaluation of the mandibular third molar impaction and planning of their atypical removal. Using this program surgeon improves preoperative evaluation of the impacted third molars, reduces operative complications, operative time, postoperative complications (in particular pain, swelling, and trismus), and consequently postoperative period after the atypical removal of mandibular third molars. Therefore besides the convenience in using of the above mentioned program in everyday practice of experienced dental surgeon, it is highly valuable assistant for young specialists and is a great way of the visualization for students during the educational process. Conclusions. Planning of the operation of atypical removal of the lower third molars requires the consideration of a number of general-somatic and local clinical characteristics, the ability to interpret the anatomical structure of the tooth and the adjacent structures on X-ray diffraction and computer tomography, prediction of all possible complications for the safe operation and avoiding complications in the postoperative period, possession with a variety of surgical techniques. The computer program we have created pays attention of dental surgeons to the most advanced characteristics at the stages of diagnosis, surgical intervention and rehabilitation period, which helps to reduce the time of operation, the number of intra- and postoperative complications.